Orthorexia nervosa in society - Dominik Olejniczak; Joanna Skonieczna (Kazimierz Wielki University, 2018)
Orthorexia nervosa is a relatively new health problem, which explains limited knowledge about the phenomenon in society. Only a few empirical studies on the course of this disorder, its characteristics and prevalence have been conducted. Therefore, it is not possible to precisely estimate the scale of the phenomenon. Nevertheless, there are tools available to assess the risk of orthorexia, and methods for its treatment. It is necessary to do further research in this disorder and to educate society about its risk factors. This can translate into an improved diagnosis (and thus help to determine the scale of the phenomenon), and support the development of uniform diagnostic criteria.